Trends in prenatal diagnosis: An analysis of 40 years of Medical Subject Heading (MeSH) terms in publications - Lu, Ya‐Ling; Bianchi, Diana W. (Prenatal diagnosis, 2020)
Objective To understand the evolution of the field of prenatal diagnosis over the past four decades. Method We analyzed the publications in the journal Prenatal Diagnosis from its inception in 1980 to 2019 using Medical Subject Headings (MeSH) to examine the major research topics and trends. The results were analyzed by 10‐year intervals. Results Publications on prenatal cytogenetics, congenital anomalies and fetal imaging predominated during the first three decades, with a steady increase in molecular genetics over time. Publications on NIPT did not appear until the most recent decade and are likely under‐counted because there was no MeSH term for NIPT until 2020. Conclusion The topics covered in Prenatal Diagnosis articles have evolved considerably over the past four decades and reflect a response to advances in technology and widespread incorporation of prenatal screening and diagnosis into standard obstetric care. The strengths of this analysis are its objective nature, its use of the standard MeSH terms used for coding, and application of a novel cluster analysis to visualize trends. The analysis also pointed out the fact that MeSH terms in this sub‐specialty area are often inconsistent due to manually coding based on individual subject matter expertise.